Variação longitudinal das caracterísitcas [i.e. características] sedimentares e hidrológicas do rio Ivaí-PR em seu curso inferior - Kuerten, Sidney (2006)
This research presents the results generated by the achievements of six field works carried out in March, May, June, September, Ocutber and November, 2004. In this work, bathymetric characteristics, hydrodynamic and sedimentary features of the bottom sediments and sediment in suspension at the low course of Ivaí river were monitored. The are of study is located at 53º 00 W superior longitude and inferior latitude at 24º 00 S in the municipalities of Tapira, Herculândia and Icaraíma in Paraná state. In each of these towns, one-kilometer section along the river has been selected and subdivided into three tranverse profile to canal with 500 meter spacing, including a 1000 meter longitudinal area.Through the survey based on direct observation and supported by sytematic monitoring of some hidrologic parameters, some features of fluvial dynamicas of that river mentioned above could be quantified and analysed. The canal declivity throughout the extension of the plain is low where it decreases toward. The carving os the canal is bigger to the upstream where the full margin measures up to 15 meters. The length of the canal increases to the downstream. The speed decreases to the downstream due to minor hydraulic gradient and the interference of Paraná river in dynamics with Ivaí river. The concentration of supspended sediments reveals either a transverse and longituinal variation. The average concentration of transported sediments was 0,0123g/L which generates a total load of 775,90 tons/day of suspended sediments. In addition, it was verified a reduction in the size of bottom sediments to the downstream. In Tapira town, medium sand predominates. On the other hand, in Icaraíma town there is ocurrency of clay on the canal bed which is related to a hydraulic selection since the energy of the system decrease to the downstream.